Pengaruh Kualitas Pelayanan terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Pemediasi (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
This study aims to determine service quality based on customer loyalty and mediated by satisfaction in Village Credit Facilities. Subjects of this study include customers of village credit institutions with the total number of people. The sample size in this study was 97 people as determined by purposive sampling technique and tested by multiple linear regression analysis techniques. The results of this study indicate that service quality has a positive and significant influence on customer satisfaction. Service quality and customer satisfaction have a positive and significant impact on customer retention. Customer satisfaction can mediate the relationship between service quality and customer loyalty. From the research results, it is necessary for the company to be able to maintain and continue to improve the quality of its service, especially for those customers who are most loyal to the company's progress and who make the community or Potential customers are increasingly interested in. using the services of the LPD of the Bale Agung Kerambitan traditional village, it is possible to conduct in-depth interviews with stakeholders on this topic to obtain additional and more complete data